Awareness of glaucoma among non-medical students in South India - Puri, Sanjeev Kumar; Elangovan, Suma (International Journal of Research in Medical Sciences, 2016)
Background: Glaucoma is one of the leading causes of blindness in the world. According to World health organization glaucoma is the second leading cause of blindness worldwide. The objective was to study the level of awareness about glaucoma among students (non-medical). Methods: A questionnaire based study was conducted among 430 students (non-medical) which tests the basic knowledge about glaucoma. Results: Out of 430 students 94.18% (405/430) did not know what glaucoma was. 3.95% (17/430) have heard about glaucoma and they knew that it was a disease of the eye. Only 8 students 1.86% (8/430) were aware of the fact that glaucoma can lead to blindness. Conclusions: The level of awareness of glaucoma is very low among students (non-medical). Efforts should be made to increase the awareness among them so that not only they will subject themselves for screening but also persuade their family members, friends and relatives for the same.